Використання систем організації знань на основі онтологій у WIKI-ресурсах - Рогушина, Ю.В. (Проблеми програмування, 2022)
У статті розглядаються теоретичні основи систем організації знань (СОЗ) в інтелектуальних застосуваннях на основі онтологій. Ціллю даного дослідження є аналіз застосування різних типів СОЗ для організації та вдосконалення бази знань семантизованих Wiki-ресурсів, які містять гетерогенний мультимедійний контент великого обсягу та мають складну структуру, що інтегрує знання із різних ПрО. Розглянуто діалекти мови подання онтологій OWL та їх виразність для подання окремих випадків онтологій, що використовуються у СОЗ. Проаналізовано критерії класифікації СОЗ та сфери їх застосування. Запропоновано формальну модель онтології семантизованого Wikі-ресурсу та засоби реалізації різних видів відношень між об’єктами у середовищі Semantic MediaWiki з використанням шаблонів, розглядаються проблеми доступу до інформації у цих ресурсах з точки зору СОЗ та наводяться методи й засоби вирішення цих проблем. Представлено реалізацію запропонованого підходу на прикладі портальної версії Великої Української Енциклопедії (е-ВУЕ). The paper considers the theoretical foundations of knowledge organization systems (KOSs) in intelligent ontology-based applications. The aim of this study is to analyze the use of different types of KOSs to organize and improve the knowledge base of semantic Wiki resources that contain heterogeneous multimedia content of large volume and have a complex structure integrated knowledge from different domains. The dialects of the OWL ontology representation language and their expressiveness for representing special cases of ontologies used in KOSs are considered. The criteria for the classification of KOSs and sphere of their usage are analyzed. Formal model of ontology for semantic Wiki resource is proposed. This model is integrated with various implementing means for different types of relations between objects in the Semantic MediaWiki environment based on templates. Problems of access and retrieval of information in these resources and methods of their solving from the KOSs point of view are considered. The software implementation of the proposed approach with the example of the portal version of the Great Ukrainian Encyclopedia (e-VUE) is realized. The urgency of the problem intensifies by the need for national information resources in martial law situation, for which the determining factors of effective information processing are both the ability to obtain satisfaction of complex information needs and the relevance of the information obtained. This increases the importance of official government portals that integrate reliable data from various fields of knowledge and prevent possible misrepresentation (both accidental and malicious) of information in resources with open content generation.